2022
DOI: 10.3390/mi13050705
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Design of Surface Acoustic Wave Sensor Based on Langasite Coplanar Integration with Multiple Parameters

Abstract: In the harsh environment of high temperature and high rotation, a single parameter is difficult to satisfy the multi-parameter test requirements of aerospace metallurgy. Therefore, a multi-parameter coplanar integrated surface acoustic wave (SAW) sensor based on Langasite (LGS) is proposed. In this paper, the optimal cut for different measurement parameters is analyzed, and the optimal cut to temperature, pressure and vibration are obtained. The simulation results show that (0°, 138.5°, 25°) LGS has superior s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The optimal cut and propagation direction for different sensing units must be carefully designed. A previous study has shown that optimal sensitivity can be achieved for temperature and pressure sensors for crystals with (0°, 138.5°, 25°) and (0°, 138.5°, 30°) cuts, respectively 30 . Due to the symmetry of the LGS, a reasonable layout design can be achieved with multiple parameters, as shown in Fig.…”
Section: Integrated Tph Sensor Structurementioning
confidence: 99%
“…The optimal cut and propagation direction for different sensing units must be carefully designed. A previous study has shown that optimal sensitivity can be achieved for temperature and pressure sensors for crystals with (0°, 138.5°, 25°) and (0°, 138.5°, 30°) cuts, respectively 30 . Due to the symmetry of the LGS, a reasonable layout design can be achieved with multiple parameters, as shown in Fig.…”
Section: Integrated Tph Sensor Structurementioning
confidence: 99%